Pertanggungjawaban terhadap Tindak Pidana Penyelundupan Sepeda Motor Harley oleh Direktur PT. Garuda Indonesia - I Dewa Gede Pramana adhi; I Nnyoman Gede Sugiartha; I Made Minggu Widyantara (Jurnal Konstruksi Hukum, 2021)
Indonesia is a developing country where each region has its own natural wealth. This advantage cannot be used because there are many people who send out of the region without permission and vice versa, goods from outside countries are smuggled into Indonesia only to avoid the applicable taxes. This study aims to examine the regulation of smuggling in criminal law in Indonesia and reveal the responsibility of the director of PT. Garuda Indonesia, which carried out the act of smuggling luxury motorcycles. This research is a type of normative legal research conducted with research methods based on legal materials, while the problem approach used is a legislative and conceptual approach. Sources of data used are primary and secondary legal materials. Another bad example is shown by one of the people who has a big name in Indonesia, the smuggling case by the president of Garuda Indonesia is an illustration of how weak the law in Indonesia is and this incident has resulted in criminal and administrative sanctions. The results of the study indicate that the regulation of smuggling crimes in Indonesia is contained in Law Number 17 of 2006 concerning Customs. Handling of violations of customs provisions is more focused on the fiscal settlement, namely in the form of payment of a sum of money to the State in the form of a fine. The criminal liability of smugglers is regulated in Law No. 17 of 2006 the president director of PT. Garuda Indonesia is threatened with criminal and administrative sanctions